Macro- and micronutrient intakes among severely malnourished under-five children during the economic crisis in Yogyakarta - Endy P Prawirohartono; Atiek Werdiningsih (Indonesian Pediatric Society, 2003)
Objective To evaluate macro and micronutrient intakes amongunder five-year children with severe malnutrition during the periodof economic crisis.Methods We conducted a longitudinal study from August untilNovember 2000 in Bantul and Sleman districts, Yogyakarta Spe-cial Territory of Indonesia. Two-weekly home visits were performedto collect data about food intakes.Results Of 46 children, 26 experienced an improvement in nutri-tional status, whereas 20 children did not. The median intakes ofmacro and 8micronutrients were lower than the RecommendedDaily Allowances (RDA), ranged from 22% (vitamin C) to 69%(phosphorus), except for vitamin A (406%). The median intakes ofprotein, vitamin A, thiamin, vitamin C, calcium, iron and phospho-rus were higher in severely malnourished children who experiencedimprovement in nutritional status compared to children who didnot, and in breastfed compared to non-breastfed, but Mann WhitneyU-test was not able to detect significant differences (p>0.05). Strati-fication using age group showed that calories and thiamin intakesof older children (348 months) were lower than those of youngerchildren (Kruskal Wallis tests p = 0.016 and 0.022 respectively).Conclusions The macro and micronutrients intakes of severelymalnourished under five-year children were lower than RDA, ex-cept for vitamin A. There were differences in nutrient intakes ac-cording to the improvement in nutritional status and age group